O gerenciamento de resultados visto sob o aspecto ético - Luis Carlos Barbosa dos Santos (2014)
The earnings management can produce a distortion in the results of companies, modifying the true picture of the organization that accounting should portray. Identifying the motives that lead to her practice evokes ethical questions because the results manage to meet certain incentives may prejudice some of the interest groups in the disclosure of the entity. Thus, the objective of this study was to analyze the perceptions of accounting professionals on earnings management under the ethical point of view. Were used two attributes of the construct of moral intensity of Jones T. M., social consensus and magnitude of consequences, because they are directly related to the focus of this research. Therefore, we applied in a questionnaire to 220 accountants regularly enrolled in CRCMG, containing a description of the four scenarios, in which a manager, motivated by increasing their pay, have the option of whether or not to engage in a practice of earnings management, with favorable and unfavorable financial consequences to their company. The intensity of ethical judgment and moral intent (reaction) of respondents, front a practice of earnings management that involves an ethical dilemma, were influenced by their perceptions of what intensity the motives are considered moral or immoral by most people involved in company, and what intensity are the likely financial consequences for the company. Was perceived that ethical judgments of the respondents were not unanimous in considering the behavior of managing results as moral or immoral in the simulations presented: in scenarios A and B where the behavior exhibited was unethical, 53% and 62% of responses, respectively, indicated the practice as immoral. However, 14% and 13% of respondents in scenarios A and B, respectively, to understand how moral; scenarios C and D of ethical behavior, 67% and 60% of respondents, respectively, indicated the practice as moral, in contrast, 11% and 13 % of respondents in scenarios C and D, respectively, understood it as immoral. Likewise, the moral intentions of the respondents were not unanimous in disapproving or encourage the practice of earnings management: in scenarios A and B, 56% and 66% of respondents, respectively, had the intention to disapprove the practice, however, 14% and 11% of respondents, in scenarios A and B, were intended to encourage her; scenarios C and D, 64% and 55% of responses, respectively, were intended to encourage the practice, however, 14% of respondents in scenarios C and D, were intended to reproach her. It can be concluded, according to the responses of 220 accounting professionals, the ethical analysis of the practice of earnings management reflects the individual's perception of what is moral consensus by a group attributed to the behavior, and what is the financial impact practice in the organization.